Programming from specifications - Morgan, Carroll 1952- (Prentice Hall international series in computer science, 1994)
Providing a thorough treatment of most elementary programme development techniques, this revised edition covers topics such as procedures, parameters, recursion and data refinement, with the integration of specification, development and coding, based on ordinary (classical) logic. This second edition features: substantial restructuring of earlier material, streamlining the introduction of programming language features; simplified presentation of procedures, parameters and recursion; an expanded chapter on data refinement, giving the much simpler laws that specialize to functional abstractions; a new chapter on recursive types (trees etc) and appropriate control structures; and, following the original concluding case study, two completely new ones: "the recursive treatment of the largest rectangle under a histogram", and a specification and extended developnent of an electronic mail system (including limited concurrency).